Talkin’ or talking? Phonological variation in the speech of London teenagers - Costin-Valentin Oancea (Bucharest Working Papers in Linguistics, 2015)
This paper analyses the (ing) variable in the speech of London teenagers. The study is based on a corpus consisting of approximately five hours of speech collected at Queen Mary’s College, University of London, in October 2012. I argue that the nonstandard form [n], usually associated with the speech of boys is frequently used by girls, contrary to the findings found in the literature on (ing).